Rituals, monuments and commemorations after (mass) traumatic events - Netten, Yosee (Array, 2009)
Throughout mankind, rituals have been part and parcel of man’s heritage, and have helped us understand and deal with important life-events and life-transitions such as birth, marriage and death. Death may be the result of a natural cause, but death can also occur unexpectedly and violently, as is the case when people are killed by disasters or during man-made disasters such as wars and violent actions such as terrorist attacks. For individuals, for communities and for nations, rituals can transmit an unspoken, often implicit yet very important message of consolation, support, recognition and understanding. Monuments and commemoration rituals have also been part of man’s cultural heritage as a way of dealing with these adversities of life. Rituals have often been performed in the proximity of these monuments. Why are monuments of such importance? And why does man require and perform commemoration rituals after tragic events? What functions do mourning- rituals have when it comes to dealing with the chaos after disasters, and how can they be helpful in the process of bereavement? These issues are illustrated with cases and examples.